Big data analytics from strategic planning to enterprise integration with tools, techniques, NoSQL, and graph - Loshin, David, 1963- (Elsevier,Morgan Kaufmann, 2013)
A short guide for managers to introduce big data technology to their organizations and change the culture and expectations around information management.